Upaya Pencegahan Stunting dengan Edukasi Gizi di Kampung Pangan Inovatif Posyandu Melati Deswita Plaju - Anita Rahmiwati; Windi Indah Fajar Ningsih; Sari Bema Ramdika; Yuliarti; Desri Maulina Sari; Fatria Harwanto; Fatmalina Febry; Indah Purnama Sari; Indah Yuliana; Ditia Fitri Arinda; Ira Dewi Ramadhani; Siti Rachmi Indahsari; Ahmad Adi Suhendra; Rully Mufarika (Jurnal SOLMA, 2023)
Background: Stunting is a nutritional problem caused by insufficient food intake for a long time. Routine exclusive breastfeeding for 6 months and followed by the provision of nutritious weaning foods is one of the efforts to prevent stunting. Purpose: community service activities are to provide knowledge about the risk factors and causes of stunting, provide knowledge about the potential of tempeh as a potential food to prevent stunting, provide knowledge and skills on how to make weaning food. Method: this activity is a collaboration between TJSL PT KILANG PERTAMINA INTERNATIONAL RU III and the Faculty of Public Health, Sriwijaya University. Participants consisted of cadres and mothers of toddlers at Melati Deswita Plaju integrated health care. The activities carried out were counseling on preventing stunting, counseling on potential food tempeh preventing stunting, story telling, let's eat tempeh. Result: as many as 85% of respondents have good knowledge after being given counseling related to stunting. Conclusion: there is an increase in knowledge where the percentage of respondents who have a good category increases after the extension activities are carried out.   Keywords: stunting, tempeh, toddlers, weaning foods, integrated health care